Peripheral artery disease is a coronary heart disease risk equivalent among both men and women: results from a nationwide study. (29th August 2020) - Subherwal, Sumeet; Patel, Manesh R; Kober, Lars; Peterson, Eric D; Bhatt, Deepak L; Gislason, Gunnar H; Olsen, Anne-Marie Schjerning; Jones, William S; Torp-Pedersen, Christian; Fosbol, Emil L
Abstract: Aims: Lower extremity peripheral artery disease (PAD) has been proposed as a 'coronary heart disease (CHD) risk equivalent'. We aimed to examine whether PAD confers similar risk for mortality as incident myocardial infarction (MI) and whether risk differs by gender. Methods: Using nationwide Danish administrative registries (2000–2008), we identified patients aged ≥40 years with incident PAD (PAD only, n = 35, 628), incident PAD with a history of MI (PAD + MI, n = 7029), and incident MI alone (MI alone, n = 71, 115). Results: Patients with PAD only tended to be younger, female, and have less comorbidity than the other groups. During follow up (median 1051 d, IQR 384–1938), we found that MI-alone patients had greater risk of adverse outcomes in the acute setting (first 90 d); however, the PAD-only and PAD + MI groups had higher long-term mortality at 7 years than those with MI alone (47.8 and 60.4 vs. 36.4%, respectively; p < 0.0001). After adjustment, the PAD-only and PAD + MI groups had a higher long-term risk for mortality [hazard ratio (HR) 1.47, 95% confidence interval (CI) 1.44–1.51; and HR 1.65, 95% CI 1.58–1.72, respectively], cardiovascular mortality (HR 1.30, 95% CI 1.26–1.34; and HR 1.71, 95% CI 1.62–1.80, respectively), and composite of death, MI, and ischaemic stroke, 95% CI HR, 1.38, 95% CI 1.36–1.42; and HR 1.68, 95% CI 1.61–1.75, respectively). The greater long-term risks of PAD were seen for both women and men. Conclusions: Both women and men with incident PAD have greater long-term risks of total and cardiovascular mortality vs. those with incident MI. PAD should be considered a CHD risk equivalent, warranting aggressive secondary prevention.